2009
DOI: 10.1016/j.yfrne.2009.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of estrogens following ischemic stroke

Abstract: Our laboratory has investigated whether and how 17β-estradiol (E2) protects the brain against neurodegeneration associated with cerebrovascular stroke. We have discovered that low, physiological concentrations of E2, which are strikingly similar to low-basal circulating levels found in cycling mice, dramatically protect the brain against stroke injury, and consequently revealed multiple signaling pathways and key genes that mediate protective action of E2. Here we will review the discoveries comprising our cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
160
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 192 publications
(172 citation statements)
references
References 114 publications
(193 reference statements)
8
160
1
3
Order By: Relevance
“…Therefore, we hypothesize that the relatively modest effect on localized GM sparing using VBM may be due to a lack of direct neuroprotective effects of natalizumab. Estrogens, in contrast, have been shown to be neuroprotective in a variety of neurologic disease models (Bode et al., 2008; Engler‐Chiurazzi, Brown, Povroznik, & Simpkins, 2017; Spence & Voskuhl, 2012; Suzuki, Brown, & Wise, 2009), including estriol treatment on cognitive electrophysiologic and neuropathologic outcomes in the MS model (Ziehn, Avedisian, Dervin, O'Dell, & Voskuhl, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we hypothesize that the relatively modest effect on localized GM sparing using VBM may be due to a lack of direct neuroprotective effects of natalizumab. Estrogens, in contrast, have been shown to be neuroprotective in a variety of neurologic disease models (Bode et al., 2008; Engler‐Chiurazzi, Brown, Povroznik, & Simpkins, 2017; Spence & Voskuhl, 2012; Suzuki, Brown, & Wise, 2009), including estriol treatment on cognitive electrophysiologic and neuropathologic outcomes in the MS model (Ziehn, Avedisian, Dervin, O'Dell, & Voskuhl, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Further, we have shown that treatment with estrogens and estrogen receptor ligands prevented both cortical and cerebellar GM atrophy by MRI, which correlated with preserving axons, neurons, and synapses in EAE (Itoh et al., 2017; Kim et al., 2018; MacKenzie‐Graham et al., 2012). Consistent with this, treatment with estrogens has been associated with neuroprotection in mouse models of ischemic stroke, Alzheimer's disease, Parkinson's disease, and Huntington's disease (Bode et al., 2008; Morissette, Al Sweidi, Callier, & Di Paolo, 2008; Suzuki et al., 2009; Yue et al., 2005). …”
Section: Discussionmentioning
confidence: 99%
“…Sex hormones not only alter procoagulant protein expression (Lowe et al , 2004 ) and the function of blood and vascular cells (Kadir et al , 1999 ;Butenas and Mann , 2002 ;Leng et al , 2004 ), but differences in platelet function (Liao et al , 2001 ;Suzuki et al , 2009 ) and in thrombosis activity (Bailey et al , 2009 ) have also been noted. Estrogen is to a degree neuroprotective (Liao et al , 2001 ;Suzuki et al , 2009 ;Selvamani and Sohrabji , 2010 ) in certain cases of induced cerebral ischemia, as females appear to suffer less severe consequences of stroke, including lesser neural tissue loss, than their male counterparts (McCullough and Hurn , 2003 ;Suzuki et al , 2009 ). In the absence of ovarian hormone production at menopause, females are again at higher risk to strokes than their male counterparts, and this risk continues to increase with age, as women have a longer life expectancy than men (Mitka , 2006 ;Suzuki et al , 2009 ).…”
Section: Introductionmentioning
confidence: 99%
“…Estrogen is to a degree neuroprotective (Liao et al , 2001 ;Suzuki et al , 2009 ;Selvamani and Sohrabji , 2010 ) in certain cases of induced cerebral ischemia, as females appear to suffer less severe consequences of stroke, including lesser neural tissue loss, than their male counterparts (McCullough and Hurn , 2003 ;Suzuki et al , 2009 ). In the absence of ovarian hormone production at menopause, females are again at higher risk to strokes than their male counterparts, and this risk continues to increase with age, as women have a longer life expectancy than men (Mitka , 2006 ;Suzuki et al , 2009 ). Thus, both sex and age play an important role in the occurrence of thrombotic events and the severity of neural damage subsequent to a stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation